Surface functionalization design of carbon materials based heterogeneous catalysis for selective oxidative transformations - Yan, Yibo (2015)
The processes of alcohols selectively oxidized to corresponding aldehydes or ketones play a vital role in either industry or laboratory because of the carbonyl versatility in organic synthesis. Owing to the recyclability, heterogeneous catalysts are superior to homogeneous catalysts under a wide range of reaction conditions. Besides catalytic activity, selectivity of a heterogeneous catalyst also plays a significant role especially in fine chemical industry. Selective oxidation of benzyl alcohol mainly forms benzaldehyde serving as flavor and precursor to valuable pharmaceuticals or plastic additives, while oxidation of glycerol generates chemicals including glyceric acid, a valuable intermediate, and dihydroxyacetone, an active ingredient in sunless tanning lotions. In this study, several sets of heterogeneous catalysts based on surface-functionalized carbon materials have been synthesized to catalyze the alcohol oxidation reactions and meanwhile the intrinsic mechanism of property-performance interactions are unraveled through a variety of characterizations. Both the Sm2O3 and 3-aminopropyl triethoxysilane functionalization of CNTs supported Pd catalysts displayed the high improvement in catalytic activity whereas the content of promoter had impact on Pd particle size, electrochemical surface area, and metal-support interactions which further influenced the benzyl alcohol conversion and selectivity toward benzyl aldehyde. New understandings of catalyst design specifically focused on the catalytic preparation strategies, physicochemical characteristics of active sites, surface chemistry and the specific metal-support interactions have been discussed in detail. Recently, a “green” synthetic approach free of toxic reagents and organic solvents has been established to transform the readily prepared carbohydrate precursors to generate carbon spheres by simply using hydrothermal autoclaves at the temperature varied from 160 ˚C to 180 ˚C. Alkaline carbon nano-spheres (CNSs) prepared by hydrothermal approach and post-functionalization with alkali solutions were employed as solid base catalysts in aldol condensation between benzaldehyde and acetaldehyde to form cinnamaldehyde. The decent negative charge and alkalinity of CNSs surface were controlled by the treatment concentration of alkali solutions, leading to high selectivity superior to aqueous NaOH as the traditional catalyst. Furthermore, CNSs with varying surface alkalinity can be adopted as proper supports for highly dispersed Pd nanoparticles with well-controlled size distribution. Those optimized alkaline CNSs supported Pd catalysts demonstrated enhanced reactivities in the solvent-free selective oxidation of benzyl alcohol and the aerobic oxidation of glycerol. In-depth characterizations of their structural and electronic properties by transmission electron microscope (TEM), field emission scanning electron microscope (FESEM), Fourier transform infrared spectroscope (FTIR) and X-ray photoelectron spectroscopy (XPS) were performed to elucidate the nature of the active sites and the mechanism. The effect of electron density, size of Pd nanoparticles as well as the surface alkalinity of supports on the catalytic performance has been unveiled.